Microeconometric evidence on demand-side real rigidity and implications for monetary non-neutrality - Sarah Marit Lein; Günter W. Beck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
To appropriately model the observed slow response of real variables to nominal shocks, macroeconomic models augment nominal with real rigidities. One very popular way of modelling such a real rigidity is to assume a non-constant demand elasticity. While there has been conducted ample empirical work on the degree and importance of nominal rigidities, there exists very little direct evidence on real rigidities of the form described above so far. By using a unique, very rich data set on micro prices, quantities bought and consumer characteristics we provide comprehensive new evidence on the degree of real rigidities across several European goods markets. We find that consumer goods markets are characterized by non-constant demand elasticities. However, the data suggests that superelasticities are much smaller that what is usually assumed in macroeconomic models. We calibrate a menu-cost model augmented with demand-side real rigidiy and find that this type of real rigidity can explain only about 10% of the monetary non-neutrality observed in the data.
Keywords: E31; E50; E30; 330